Design And Performance Testing Of Automatic Hand Stackers With Electrical Systems - Nurlaela Latif; Andi Muadz Palerangi; Achmad Romadin (JoVI:JOURNAL of VOCATIONAL INSTRUCTION, 2026)
In the era of ever-evolving industrial automation, efficiency and safety in material handling processes are crucial. This study discusses the design and construction of an electric-based automatic hand stacker as an alternative solution to the manual systems that are still widely used. This system is designed to minimize human labor in the process of lifting and moving goods, as well as to improve work precision and safety. Test results show that the electric hand stacker is capable of lifting loads of up to 500 kg to a maximum height of 1.3 meters. As the load weight increases on the hand stacker, the safe lifting height decreases. This system is expected to serve as an efficient and economical alternative for small to medium-scale logistics operations.